The Chittagong hill tracts accord implementation in Bangladesh: ideals and realities - Chowdhury, Nusrat Jahan (2009)
Successful policy implementation is one of the prerequisites for establishing good governance in any country, especially when the goal is no estgablish peace. But what happens during the implementation process? In this regard, the paper focuses on the much debated Chittagong Hill Tracts (CHT) Peace Accord implementation process which granted certain degree of power and autonomy to the Regional Council (RC) to administer and ensure the political economic and cultural rights of tribal people in the hill tracts. Findings indicate that the accord suffers from clear policy standard and objectives and there is a profound lack of political commitment on the part of the government towards the implementation. Moreover, personal and institutional interests of elites (local political leaders, army and bureaucrats), ideological conflict between different tribal organiations, intra-tribal rivalry and relation of distrust between Bengali-tribal people are affecting the implementation of the policy. (Reproduced).
Keywords: Public policy - Bangladesh; Public policy